Justice in the Time of War - Lazzaretti, Fabrizio (Gondolfo, Vanni, 2003)
Duration: 01:17:00 The Turra family lost their exquisite son in Colombia. Giacomo was a poet, an anthropologist, a sensitive and by all accounts loveable boy. But Giacomo was arrested by the police, and died in their custody. The Turras refused to accept the official explanation, according to which, their son had been in possession of cocaine, and acted violently under the influence. For years they tried get justice for Giacomo but failed. Out of the Turras' story, Fabrizio Lazzaretti has fashioned a parable for our times. It seems that you cannot even secure the minute amount of dignity for your dead son. People will lie to you, and otherwise treat you with contempt. Around this revelation the film weaves a depressing tapestry of contemporary Colombia. It appears to be a place so violent that individual actions no longer mean very much. An impassioned, terrifying film.